Exploring new physics in the late Universe’s expansion through non-parametric inference - Sabogal, M. A.; Akarsu, Ö; Bonilla, A.; Di Valentino, E.; Nunes, R. C. (Springer Science and Business Media LLC, 2024)
AbstractIn this study, we investigate deviations from the Planck-$$\Lambda $$ Λ CDM model in the late universe ($$z \lesssim 2.5$$ z ≲ 2.5 ) using the Gaussian Processes method, with minimal assumptions. Our goal is to understand where exploring new physics in the late universe is most relevant. We analyze recent Cosmic Chronometers (CC), Type Ia Supernovae (SN), and Baryon Acoustic Oscillations (BAO) data. By examining reconstructions of the dimensionless parameter $$\delta (z)$$ δ ( z ) , which measures deviations of the Hubble parameter from the Planck-$$\Lambda $$ Λ CDM predictions, we identify intriguing features at low ($$z \lesssim 0.5$$ z ≲ 0.5 ) and high ($$z \gtrsim 2$$ z ≳ 2 ) redshifts. Deviations from the Planck-$$\Lambda $$ Λ CDM model were not significant between $$0.5\lesssim z \lesssim 2$$ 0.5 ≲ z ≲ 2 . Using the combined CC+SN+BAO dataset, we gain insights into dark energy (DE) dynamics, resembling characteristics of omnipotent DE, extending beyond quintessence and phantom models. DE exhibits n-quintessence traits for $$z\gtrsim 2$$ z ≳ 2 , transitioning with a singularity around $$z\sim 2$$ z ∼ 2 to usual phantom traits in $$1\lesssim z\lesssim 2$$ 1 ≲ z ≲ 2 . DE characteristics differ between scenarios ($$H_0$$ H 0 -SH0ES and $$H_0$$ H 0 -$$\Lambda $$ Λ &CMB), with $$H_0$$ H 0 -SH0ES leaning towards phantom traits and $$H_0$$ H 0 -$$\Lambda $$ Λ &CMB towards quintessence. We suggest exploring new physics at $$z\lesssim 0.5$$ z ≲ 0.5 and $$1.5\lesssim z\lesssim 2.5$$ 1.5 ≲ z ≲ 2.5 , particularly around $$z = 2$$ z = 2 , to understand cosmological tensions such as $$H_0$$ H 0 and $$S_8$$ S 8 .
Keywords: QB460-466; Cosmology and Nongalactic Astrophysics (astro-ph.CO); Nuclear and particle physics. Atomic energy. Radioactivity; FOS: Physical sciences; QC770-798; Astrophysics; Astrophysics - Cosmology and Nongalactic Astrophysics